Assessing strategy to improve dairy production and milk quality under smallholder dairying: Evidence from Ethiopia - Eyob Mengesha; Habtamu Lemma Didanna; Asrat Ayza (Acta Scientiarum. Animal Sciences, 2024)
Little information exists on effectiveness of the approach in the intervention programme delivered to smallholder dairy farmers. A comparative study was conducted to assess milk production and composition in two districts (Doyogena project area and Angacha as a control) and the associated dairy intervention. Data were collected through household survey and milk testing. The average daily milk yield of crossbred dairy cows was 6.91±1.14 litres, which was significantly (p < 0.05) different across districts. The overall mean fat, solids-not-fat, lactose, salts, protein, and total solids (TS) contents of crossbred cows’ milk were 4.71±0.83, 8.85±0.36, 4.87±0.19, 0.72±0.03, 3.23±0.13 and 13.55±0.19 percent, respectively. The milk composition was significantly (p < 0.05) different across the study areas. Milk fat content is higher than the Ethiopian standard (ES); protein is also comparable. The major constraints for dairy production in the study areas were, in descending order, feed shortage in the dry season, land scarcity, lack of improved breeds, market access, and disease prevalence. To make livestock programs more impactful, strong extension and an integrated approach that encompasses improved feeds, breeding, marketing, and better health management are crucial to alleviate the diverse constraints of smallholder dairying while enhancing productivity and the associated food and nutrition security and livelihoods.